MMP9 expression in intestinal fistula from patients with fistulizing CD and from human xenograft mouse model. Issue 2 (3rd April 2022) - Mamie, Céline; Bruckner, Ramona S.; Lang, Silvia; Shpigel, Nahum Y.; Turina, Matthias; Rickenbacher, Andreas; Cabalzar-Wondberg, Daniela; Chvatchko, Yolanda; Rogler, Gerhard; Scharl, Michael
ABSTRACT: Fistula treatment represents a major unmet medical need in the therapy of Crohn's disease (CD). Current medical therapies, such as anti-TNF antibody treatments, are often insufficient and do not achieve permanent fistula closure. Previously published data point toward a critical role for metalloproteinase-9 (MMP-9)/gelatinase B in fistula pathogenesis. The aim of this project was to investigate in detail MMP-9 expression in different fistula types and to confirm that MMP-9 is a potential target for fistula therapy in CD patients. Immunohistochemistry for total and active MMP-9, Cytokeratin 8 (CK-8) and co-staining of active MMP-9/CK-8 was performed in specimen derived from perianal fistulas, entero-enteric fistulas and fistulas from patients not responding to anti-TNF therapy. In addition, fistulas from the xenograft mouse model (anti-TNF treated or untreated) were analyzed. Total and active MMP-9 protein was detectable in cells lining the tracts of perianal and entero-enteric fistulas. Of note, total and active MMP-9 was also expressed in fistulas of CD patients non-responding to anti-TNF treatment. Interestingly, we detected considerable co-staining of active MMP-9 and CK-8 in particular in cells lining the fistula tract and in transitional cells around the fistulas. Furthermore, total and active MMP-9 are detectable in both anti-TNF treated and untreated xenograft fistulas. Taken together, our data suggest that MMP-9 is involved in fistula pathogenesis in CD patients, in fistulas of different origins and particularly in patients non-responding to anti-TNF therapy. Our xenograft fistula model is suitable for in vivo studies investigating a possible therapeutic role for MMP-9 targeting as fistula therapy.